EFEKTIVITAS PAKET PENGENDALIAN RESIKO PENYIMPANGAN IKLIM DI JAWA TENGAH(THE EFFECTIVENESS OF THE CLIMATE CHANGE RISK MANAGEMENT SCHEME IN CENTRAL JAVA) - . Sarjana; Meinarti Norma; Seno Basuki (Agromet, 2009)
This paper is summary report of study on implementation of local government designed strategies to anticipate and manage the climate change risks in Central Java. The basis of information obtained from interviews to farmers. In general, planting patterns follow schedule of water availability; therefore, farmers are more interested in talking about the lack of water compared with the excess water. According to farmers' language, climate change is the rainy season retreat. In this context, almost all respondents stated that the climate changes disrupt their farming activities. These disorders include reduction of production, planting schedule delays, increased costs of irrigation, seeds, pesticides and land management. Local agricultural agencies have been disseminating strategies to anticipate and manage the risks of climate change. Those strategies are planting reschedules, changing varieties or commodities, and improving the water management. Local governments also facilitate the implementation of those strategies, namely distribution of water pumps, and seeds according to climate prediction, and repair or construction of irrigation channels and reservoirs. Most respondents (59%) had never directly followed those socialization activities, and due to limited of the distributed facilities, only 29.87% of respondents enjoyed such facilities. However, the recipient stated that the government facilities effectively assist them in controlling the impact of climate change, and most farmers had committed the management of climate changes impacts in a manner consistent with the recommended strategy. These results show that both government assistance and collective action by farmers had the same important role in anticipating and controlling the impact of climate changes. Therefore, the government should socialize recomended strategies in a more intensive, and improve, and expand the reach of distribution facilities to implement the strategy. These efforts would stimulate farmers self-supporting as a whole, so that the programs in anticipating and controlling the impact of climate changes would be more effective.